IMPLEMENTATION OF THE MOBILE JKN PROGRAM IN PUBLIC SERVICES AT THE CANDI COMMUNITY HEALTH CENTER IN SIDOARJO REGENCY - Nike Surya Saputri; Ahmad Riyadh Umar Balahmar (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of the Mobile JKN application at the Candi Community Health Center (Puskesmas Candi) in Sidoarjo Regency as part of the digital transformation of public services. Method: The method used was descriptive qualitative, using observation, interviews, and documentation techniques. The analysis was conducted using George C. Edward III's policy implementation theory, which includes four indicators: communication, resources, disposition, and bureaucratic structure. Results: The results showed that the implementation of Mobile JKN has not been optimal. In terms of communication, there are still obstacles in socialization and digital literacy, especially among the elderly. In terms of resources, staff are sufficiently prepared, but user skills are not evenly distributed. In terms of disposition, staff attitudes are considered good and cooperative, although some patients still experience difficulties. Meanwhile, in terms of bureaucratic structure, limited SOPs and application features hinder smooth service delivery. These findings emphasize the need for increased socialization, infrastructure improvements, and regulatory strengthening so that the use of Mobile JKN can support basic health services more effectively. Novelty: This study highlights the real challenges in implementing a digital public service application in a community health center context, particularly emphasizing the gaps in communication, user skills, and bureaucratic support, which are often overlooked in digital transformation initiatives.